A Hindu Champion of Pan-Islamism: Lajpat Rai and the Khilafat Movement - Bhargav, Vanya Vaidehi (The Journal of Asian studies, 2022)
Lala Lajpat Rai is increasingly viewed in historiography as a “Hindu nationalist” with a strong affinity with Savarkarite Hindutva. This article demonstrates that during the Khilafat movement, Lajpat Rai articulated a secular Indian nationalism that was sensitive to Muslim religiosity and Indian Muslims’ extraterritorial sympathies toward the caliphate and the Muslim world. Pigeonholing the entire thought of Lajpat Rai as “Hindu nationalism” obscures a historical-intellectual juncture when a Hindu political figure like him enthusiastically supported pan-Islamism as necessary for Indian nationalism. This article complicates scholarship that portrays Hindu responses to the Khilafat movement as consisting solely of fear and counter-consolidation. More importantly, by unveiling Rai's Khilafat-era nationalism, it uncovers the intellectual and political possibility of firmly holding a Hindu identity and articulating conceptions of Indian nationhood that are at ease with Islam and the wider Muslim world.